Technology teachers' knowledge, attitudes, and practices of occupational health and safety in the school workshop - Oladiran Stephen Olabiyi; Adeneye Olarewaju A. Awofala; Wole Akinlabi (Faculty of Engineering, Universitas Negeri Yogyakarta, 2025)
The study examined technology education teachers' knowledge, attitudes, and practices of occupational health and safety in the school workshop. Also influence of technology teachers' gender was determined. The study employed the descriptive correlational survey method of research. The respondents for the study consisted of two hundred and seventy-six (276) technical college teachers. A questionnaire was used to collect data. independent samples t-test, Pearson moment correlation coefficient and multiple regression analysis were used to analyze the data collected. The study found out that there was a significant influence of gender on technology teachers' attitude and knowledge however, gender did not have significant influence on technology teachers' practice of occupational health and safety. There was a weighty relationship amid knowledge, attitude and practice towards occupational health and safety. Attitude and knowledge were significant predictors of occupational safety and health practice. Consequently, the study recommended among others that occupational safety and health training should be provided to improve technology teachers' knowledge and attitude to better predict their practice towards it, the practice of safety be stressed by the employer, who should supply workers with safety precautions and appropriate clothes (personal protection equipment) in the job, effective procedures and corrective activities should be implemented in the school workshop to prevent and reduce the occurrence of accidents.